Effectiveness of snail mucus gel (Achatina fulica Ferr) on mice (Mus musculus L.) burns - Wa Ode Harlis; Dwi Arinto Adi; Ni Made Maitri Saraswati; Jamili Jamili; Suriana Suriana; Resman Resman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aimed to determine the effectiveness of snail mucus gel (Achatina fulica) on the length of time for burns healing, burns diameter, and the percentage of burns healing in mice (Mus musculus). The type of this research was experimental with a completely randomized design (CRD) method with 20 male mice divided into five treatment groups, namely NC (Negative Control; gel basis), PC (Positive Control; Bioplacenton 10%), P1 (3% gel), P2 (4% gel) and P3 (5% gel), with four replications for each treatment. The making of burns on the back of mice was done by using metal coins that were heated to become coals with an initial diameter of 20 mm, which are affixed for 1 second. The parameters observed were the length of time for burns healing, burns diameter, and the percentage of burns healing for 16 days. The data were analyzed by using Way ANOVA (Analysis Of Variance) (α = 0.05%) and continued with the LSD (Least Significant Different) test. The results showed that snail mucus gel (A. fulica) with a gel concentration of 5% was more effective in accelerating burns healing with an average healing time of 14 days, and positive controls healed within 14. In 25 days, 4% gel recovered in 14.5 days, 3% in 15 days, and negative controls recovered in 16 days. The fastest closure of burns diameter was in gel with a concentration of 5% with a mean of burns diameter of 0.33 mm and an average percentage of burn healing of 98.35%, followed by the Bioplacenton treatment group of 10%, gel with a concentration of 4%, 3%, and the longest burns closure was in the ointment base gel group.